Chemically unidentified dissolved organic carbon: A pivotal piece for microbial activity in a productive area of the Northern Patagonian shelf. (May 2021) - Garzón-Cardona, John E.; Guinder, Valeria A.; Alonso, Cecilia; Martínez, Ana M.; Pantoja-Gutiérrez, Silvio; Kopprio, Germán A.; Krock, Bernd; Lara, Rubén J.
Abstract: The biochemical composition and fluorescence properties of DOM were assessed in relation to phytoplankton and major aquatic bacterial clades in a regenerative area of the Argentine Shelf. DOM was mainly of autochthonous biological origin, containing humic- and protein-like substances of medium degree of unsaturation and diagenesis. Biochemical-DOM accounted for 25% of total DOC, being dissolved combined amino acids (DCAA) the dominant fraction followed by free carbohydrates. Phytoplankton was the main source of serine, alanine, and valine, and particulate carbohydrates. Gammaproteobacteria abundance correlated negatively with ammonium and positively with DCAA, suggesting a coupling between ammonium consumption and refractory amino acid production. A preferential utilization of alanine, leucine and threonine as nitrogen source was inferred from the distribution of Cytophaga-Flavobacteria-Bacteroidete in relation with dissolved free amino acids (DFAA). Notably, Alpha - and Betaproteobacteria correlated with the large pool (75%) of chemically unidentified DOC and not with DCAA or dissolved combined carbohydrates. Particularly, Alphaproteobacteria (∼40% of EUB total heterotrophic bacteria) either significantly contribute to the production of the "humic", refractory fraction of marine DOM, or the latter impairs resource control on their abundance. Spatial heterogeneity inherent to coastal-shelf areas drives important regional variability in the biochemical properties of DOM. Highlights: Composition of DOM is characterized in a productive area of the SW Atlantic shelf. Alphaproteobacteria are related with humic, refractory DOM. Combined amino acids and free carbohydrates dominate the biochemical-DOM. Protistan phytoplankton are the main source of particulate carbohydrates. Ecosystem settings and microbial clades exert regional effects on carbon paths.